Author Correction: Highly confined epsilon-near-zero and surface phonon polaritons in SrTiO3 membranes - Xu, Ruijuan; Crassee, Iris; Bechtel, Hans A.; Zhou, Yixi; Bercher, Adrien; Korosec, Lukas; Rischau, Carl Willem; Teyssier, Jérémie; Crust, Kevin J.; Lee, Yonghun; Gilbert Corder, Stephanie N.; Li, Jiarui; et al. (Nature communications, 2024)
Correction to: Nature Communicationshttps://doi.org/10.1038/s41467-024-47917-x, published online 04 June 2024 In this article the grant number #200020_201096 relating to the Swiss National Science Foundation was omitted. The original article has been corrected.